Preface to the Mediterranean Conference on Three Decades of Neutrosophic and Plithogenic Theories and Applications (MeCoNet 2024), University of Messina, Sicily, Italy, 24 - 25 September 2024 - Florentin Smarandache; Giorgio Nordo (Neutrosophic Sets and Systems)
This volume contains the proceedings of the Mediterranean Conference on Neutrosophic Theory (MeCoNeT 2024), held at the Accademia Peloritana dei Pericolanti of the University of Messina on September 24-25, 2024. The event was organized by the MIFT Department (Mathematics, Computer Science, Physics, and Earth Sciences) of the University of Messina, marking the first international congress on neutrosophic theories outside the Americas. This milestone has firmly established the Mediterranean region as a key hub for research in the rapidly growing field of neutrosophic theory.